2006
DOI: 10.1055/s-2006-944959
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics after endoscopic submucosal injection of epinephrine in patients with nonvariceal upper gastrointestinal bleeding: a matter of concern

Abstract: We report about detailed hemodynamic changes and one major cardiac complication occurring after submucosal injection of epinephrine (1 : 10 000) for management of upper gastrointestinal bleeding in a series of four consecutive patients. Cardiac contractility and afterload, determined by the cardiac index and the systemic vascular resistence index (SVRI), were assessed by transpulmonary thermodilution using the Pulse Contour Cardiac Output monitoring system (PiCCO; Pulsion Medical Systems, Munich, Germany), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In this study, initial hemostasis was reached in 96% and recurrent bleeding was observed only in 4%. One should be cautious when using epinephrine in patients with underlying coronary artery disease or cardiac arrhythmias, since sys- temic absorption may occur and result in myocardial events (55).…”
Section: Treatmentmentioning
confidence: 99%
“…In this study, initial hemostasis was reached in 96% and recurrent bleeding was observed only in 4%. One should be cautious when using epinephrine in patients with underlying coronary artery disease or cardiac arrhythmias, since sys- temic absorption may occur and result in myocardial events (55).…”
Section: Treatmentmentioning
confidence: 99%
“…Several hemostasis procedures applied to MWT include endoscopic band ligation, 15–18 endoscopic injection therapy, 17,19–25 endoscopic electrocoagulation 15,26,27 and selective arterial embolization 28,29 . Previous reports indicated the efficacy of hemoclips for MWT 19,20,30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Most patients with MWT do not require endoscopic hemostasis and blood transfusion, [2][3][4][5] but several reports have indicated that patients with wide tears on the gastroesophageal mucosa suffered from massive bleeding and required endoscopic hemostasis. [11][12][13][14] Several hemostasis procedures applied to MWT include endoscopic band ligation, [15][16][17][18] endoscopic injection therapy, 17,[19][20][21][22][23][24][25] endoscopic electrocoagulation 15,26,27 and selective arterial embolization. 28,29 Previous reports indicated the efficacy of hemoclips for MWT.…”
Section: Introductionmentioning
confidence: 99%
“…40 Submucosal injection of epinephrine potentially can result in systemic effects such as severe hypertension, ventricular tachycardia, and intestinal ischemia; however, case reports regarding these complications are rare and result from procedures in which the goal of therapy was hemostasis rather than EMR and during which higher concentrations of epinephrine (1:10,000) were used. [41][42][43] Staining dye (ie, diluted indigo carmine or methylene blue) is frequently added to the injection solution to facilitate identification of the lateral and deep margins of the target lesion before and during the resection process. The staining dye may also improve recognition of muscularis propria injury and intraprocedural perforation.…”
Section: Submucosal Injection Solutionsmentioning
confidence: 99%